Christian and traditional African attitudes towards HIV/AIDS - Chepkwony, Adam K. A. (African Ecclesial Review, 2004)
ACCORDING to the World Health Organization (WHO), AIDS is the fourth-leading cause of death worldwide and the leading cause of death in sub-Saharan Africa. Different views advanced as causes of HIV/AIDS from both the Christian and African traditional circles, have played a significant role in mystifying the epidemic in Africa and indeed in the world, thereby contributing immensely to the prevalence of the world-killer. Africa continues to register heavy death tolls from the epidemic due to the prevailing attitudes by different Christian and traditional African groups on the deadly scourge. This article illustrates that the rampant negative attitudes towards HIV/AIDS are unethical and that they also hasten the death of the sufferers. I shall also observe that modern anti-HIV/AIDS campaigns that insist on the use of the condom for protection, encourage promiscuity and free sex instead of discouraging it. Besides, these campaigns are insensitive to the traditional African cultural norms towards the act of sex. I shall further discuss some recent encouraging developments in regard to HIV/AIDS and propose some ethical issues for consideration as a way forward for Christians, African traditionalists, counsellors and other helpers in their attempt to combat the deadly scourge.
Keywords: AIDS (Disease); Christianity and African religions; Culture and Christianity; HIV (Viruses); Health and religion; Sexual ethics; Taboo